Plasma phospho‐tau181 increases with Alzheimer's disease clinical severity and is associated with tau‐ and amyloid‐positron emission tomography. Issue 8 (4th April 2018) - Mielke, Michelle M.; Hagen, Clinton E.; Xu, Jing; Chai, Xiyun; Vemuri, Prashanthi; Lowe, Val J.; Airey, David C.; Knopman, David S.; Roberts, Rosebud O.; Machulda, Mary M.; Jack, Clifford R.; Petersen, Ronald C.; et al.
Abstract: Introduction: We examined and compared plasma phospho‐tau181 (pTau181) and total tau: (1) across the Alzheimer's disease (AD) clinical spectrum; (2) in relation to brain amyloid β (Aβ) positron emission tomography (PET), tau PET, and cortical thickness; and (3) as a screening tool for elevated brain Aβ. Methods: Participants included 172 cognitively unimpaired, 57 mild cognitively impaired, and 40 AD dementia patients with concurrent Aβ PET (Pittsburgh compound B), tau PET (AV1451), magnetic resonance imaging, plasma total tau, and pTau181. Results: Plasma total tau and pTau181 levels were higher in AD dementia patients than those in cognitively unimpaired. Plasma pTau181 was more strongly associated with both Aβ and tau PET. Plasma pTau181 was a more sensitive and specific predictor of elevated brain Aβ than total tau and was as good as, or better than, the combination of age and apolipoprotein E ( APOE ). Discussion: Plasma pTau181 may have utility as a biomarker of AD pathophysiology and as a noninvasive screener for elevated brain Aβ.